The Effect of Household Dependency Ratio on the Mental Health of Workforce: Evidence From China - Fang, Dongli (Frontiers in Public Health, 2022)
Based on the Chinese General Social Survey (CGSS) 2010, this paper investigates the relationship between household dependency ratio and the mental health of household workforce. The empirical results verify the negative impacts of both household old age dependency ratio and child dependency ratio on the mental health of workforce, and find that the negative effect of old age dependency ratio is greater than that of child dependency ratio. Moreover, the depression source of young workforce mainly comes from child dependency ratio, while the depression source of older workforce comes from old age dependency ratio. The mental health of workforce in poor regions is impaired by household dependency burden, but we find no same evidence in rich regions. The old age dependency ratio negatively affects the mental health of workforce by household health care burden, while child dependency ratio negatively affects the mental health of workforce by education expenditure pressure. Our findings provide evidence on how household structure affects the welfare of family, and give implications to the improvement of residents’ health.